Writing an Abstract for a Scientific Conference - Simkhada, P; Van Teijlingen, E; Hundley, V; Simkhada, BD (Kathmandu University Medical Journal, 2015)
For most students and junior researchers, writing an abstract for a poster or oral presentation at a conference is the first piece they may write for an audience other than their university tutors or examiners. Since some researchers struggle with this process we have put together some advice on issues to consider when writing a conference abstract. We highlight a number of issues to bear in mind when constructing one’s abstract. DOI: http://dx.doi.org/10.3126/kumj.v11i3.12518 Kathmandu Univ Med J 2013; 43(3):262-265